The Influence of Reward, Punishment, and Work Culture on Employee Performance PT Pratama Palm Abadi - Hendri Diansyah; Endah Dewi Purnamasari; Try Wulandari (ProBisnis : Jurnal Manajemen, 2023)
This study aims to determine how much influence Reward, Punishment, and Work Culture have on employee performance by conducting tests using SPSS version 23. This research was conducted on respondents who were employees at PT Pratama Palm Abadi with a total sample size of 70 respondents. This research uses quantitative methods and the analysis used is multiple linear regression analysis. The results of the first regression analysis prove that reward (X1) has a significant effect on employee performance, which means that H1 is proposed to be accepted. With the increase in rewards, it has a positive impact on improving employee performance. This means that reward has a positive effect on employee performance. The second regression result proves that punishment (X2) has a positive effect on employee performance, which means that H2 is accepted. It is very necessary to be firm in giving punishment so that it can improve the discipline of employee performance. The third regression result proves that work culture (X3) has a positive effect on employee performance, which means that the proposed H3 is accepted. The higher the work culture, the effect of increasing employee performance. Together the Reward (X1), Punishment (X2) and Work Culture (X3) variables have a positive effect on employee performance.